2018
DOI: 10.1111/jppi.12261
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Provision of Day Services in Ireland to Adult Persons With Intellectual Disability

Abstract: Internationally, changes are advocated in the support available to persons with intellectual disability. Socially inclusive personalized arrangements are intended to replace congregated and segregated day services. The study examines the changes in the provision of day services within Ireland over a 5‐year period when new policies were being promoted but at time of economic stringencies. Secondary analysis was carried out on data extracted from the National Intellectual Disability Database on all persons aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…15 In Ireland, data in the National Intellectual Disability Database from 2014 showed that of those people with ID participating in any kind of day services, 14.8% participated in a sheltered workshop and 9.9% received 'employment support', which included working in the open labour market. 16 Other comparative research confirms a picture of very low employment participation rates for people with ID in Europe. 17 Even when people with ID are active in the labour market, their experience of employment differs from that of other workers.…”
Section: Labour Market Participationmentioning
confidence: 84%
“…15 In Ireland, data in the National Intellectual Disability Database from 2014 showed that of those people with ID participating in any kind of day services, 14.8% participated in a sheltered workshop and 9.9% received 'employment support', which included working in the open labour market. 16 Other comparative research confirms a picture of very low employment participation rates for people with ID in Europe. 17 Even when people with ID are active in the labour market, their experience of employment differs from that of other workers.…”
Section: Labour Market Participationmentioning
confidence: 84%
“…Outreach programmes served 3% of this cohort. These proportions are broadly reflective of all adult persons using these day services (McConkey, Kelly, Craig, & Keogh, ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed for adults of all ages, care centres are the dominant form of day service provision in the Republic of Ireland and in the past 5 years the proportion of persons attending these centres has grown across all ability levels (McConkey et al., ). In part this may result from pressures to quickly find placements for leavers from schools and training centres during times of economic stringencies on health spending when staffing ratios in particular dis‐improved (Health Manager, ).…”
Section: Discussionmentioning
confidence: 99%
“…Covid-19 has dramatically changed how services for people with disabilities operate in Ireland. Disability services over the past 150 years have gone through many transformations from support for people with disabilities through institutionalisation in large congregated settings to a more person-centred rights-based approach within services (Dukelow and Considine, 2018; McConkey et al., 2018). Since the 1990s, in light of how the global Disability Rights Movement discredited the medical model based approach, Ireland began another transformative period towards a more social model of service provision (Dukelow and Considine, 2018; Garcia Iriarte, 2016).…”
mentioning
confidence: 99%
“…Since the 1990s, in light of how the global Disability Rights Movement discredited the medical model based approach, Ireland began another transformative period towards a more social model of service provision (Dukelow and Considine, 2018; Garcia Iriarte, 2016). The shift towards the social model of person-centred, rights-based approach evident in the policies and legislation 1 has become even more pronounced in the 2010s (McConkey et al., 2018). Due to the pandemic, we are now in the midst of another transformative period, which is not only indicating long-term, major changes in the provision of services, but also uncovering the nature of the mode of delivery that has emerged of the past number of years.…”
mentioning
confidence: 99%